The effect of subgingival irrigation of Gambir (Uncaria gambir [Hunter] Roxb) catechin to the number of Actinobacillus Actinomycetemcomitans in the gingival sulcus of periodontitis mice - Lestari, Citra (Universitas Padjadjaran, 2011)
Periodontitis is one of periodontal disease that the main cause is bacteria, especially Actinobacillus actinomycetemcomitans (AA). One of the treatments for these conditions can be done with subgingival irrigation using Gambir catechin (Uncaria gambir [Hunter] Roxb). Catechins are polyphenolic compounds and have antibacterial effects. Based on its advantages, a cathecin effect may decrease the amount of AA in periodontitis and help the healing. The aim of this study was to know the effect of subgingival irrigation of the Gambir catechin to the amount of AA in periodontitis mice. Twelve mice, 3 months age, 200-250 gr in weight, with the anterior gingival sling with yarn was made for periodontitis condition. The mice were divided into four groups treatment: Treatment with aquadest, Gambir catechin I, Gambir catechin II, and chlorhexidine 0.2%. Subgingival irrigation performed after visible signs of periodontitis with 2 times daily for seven days. AA retrieval was done using paper points inserted in the gingival sulcus and grown in BHI agar with bacitracin 5 units/ml (modification). The number of AA was then counting with colony counters. Study result showed a significant difference (p <0.05) between aquadest treatment group with Gambir catechin I, Gambir catechin II, and chlorhexidine 0.2%. But there was no significant difference between Gambir catechin I and II. The conclusion of this study indicated that subgingival irrigation of Gambir catechin I and II could decrease the amount of AA but there was no statistical difference between the two groups. This means that Gambir catechin in solutions and effervescent didn't affect the activity of a substance in it. It was shown that catechins can be used as an alternative to the condition of periodontitis.